Learning for earning : your route to success. Student workbook - Wanat, John A.; Pfeiffer, E Weston; Gulik, Richard Van (Illinois : The Goodheart-Willcox Company, Inc., 2009)
Designed to help students review content, apply knowledge, and develop critical-thinking skills. A wide variety of activities are provided for various learning styles. This supplement is a consumable resource, designed with perforated pages so that a given chapter can be removed and turned in for grading or checking.